ASSESSING PORTFOLIO EFFICIENCY THROUGH RISK-ADJUSTED MEASURES: A COMPARATIVE ANALYSIS OF MARKOWITZ AND SINGLE INDEX MODELS - Steven Imanuel; Rousilita Suhendah (Graduate Program of Universitas Tarumanagara, 2026)
This study is conducted to evaluate and compare the effectiveness of portfolios formed using the markowitz model along with the single index model based on return, risk, and investment performance evaluation ratios. The research method uses data from IDX80 companies. The results show that the portfolio formed using the markowitz model yield a return of 0.06% in one day, accompanied by a risk level of 0.007%, while the single index model generates an elevated return of 0.24% with a risk of 1.51%. In terms of performance, based on the sharpe ratio, the highest value was obtained in the markowitz portfolio at 0.059330, while the highest treynor ratio and jensen ratio were found in the single index model, yielding values of 0.002264 and 0.002142, respectively. These results indicate that the markowitz model is more efficient in minimizing risk, while the single index model is superior in maximizing returns. Thus, the markowitz model is better suited for investors who are risk-averse, while the single index model is fitted for moderate to aggressive investors who prioritize higher potential returns despite greater risk.